The Korean and Indonesian variant of nocturnally periodic form of Brugia malay! (Nematoda:Filarioidea) the causative agent of filariasis. - FA Sudjadi, FA Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Backgound: The nocturnally periodic form of B.malay/ was reported as health problem both in Cheju, Korea and Bireuen, Aceh, Indonesia. The filarial worm was transmitted respectively by Ae.togoi in Korea and An.barbirostris in Indonesia.Objectives: To know any difference of microfilarial behaviour in peripheral blood by meta-analisis on available data published by previous workers.Methods: Using Aikat and Das formula of statistical analysis.Results: B.malayi s microfilariae tend to present at peripheral blood at day time among cases in Cheju, Korea more than those in Bireuen, Aceh, IndonesiaConclusion: B.malayis microfilariae in Cheju, Korea still had tendency to show (nocturnally) subperiodicmore than those in Bireuen, Aceh. Key words: filariasis - B.ma/ayis microfilaria variant - nokturnally periodic - nocturnally subperiodic